Предмет: Математика,
автор: lieqwa
ПОМОГИТЕ ПОЖАЛУЙСТА СРОЧНО НУЖНО РАССПИСАТЬ
Приложения:
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
( 7,1х - 6,3) - ( 6,7х - 7,9) = 0
7,1х - 6,3 - 6,7х + 7,9 = 0
0,4х + 1,6 = 0
0,4 х = -1,6
х= - 1,6 : 0,4
х= -4
Ответ : х= - 4
-(4,1х - 5,5х) - ( 7,3х + 3,6) = - 5,3х
-4,1х + 5,5х - 7,3х - 3,6 = - 5,3х
- 5,9х - 3,6 = - 5,3х
- 5,9х + 5,3х = 3,6
- 0,6х = 3,6
х= 3,6 :(-0,6)
х= -6
Ответ: х= -6
(7,4х - 12,3х) - (1,56 - 2,3х) = 2,6х
7,4х - 12,3х - 1,56 + 2,3х = 2,6х
-2,6х - 1,56 = 2,6х
- 2,6х - 2,6х = 1,56
- 5,2х = 1,56
х= 1,56 : (-5,2)
х= - 0,3
Ответ : х= - 0,3
Похожие вопросы
Предмет: Английский язык,
автор: Twinsister11
Предмет: Русский язык,
автор: anjbavidova
Предмет: Русский язык,
автор: Аноним
Предмет: Биология,
автор: Валерьян0чка
Предмет: Математика,
автор: matvejsharapov1